Dinamika Perdebatan “Syariat Islam” Dalam Historisasi Piagam Jakarta (Jakarta Charter) - Aini Shalihah; fahri Hozaini (Fakultas Syariah Univeritas Islam Madura, 2022)
In the Indonesian context, we find the principle of Belief in One God, which is contained in the preamble to the 1945 Constitution. And the Jakarta Charter is part of the body of the constitution which has now been transformed into Pancasila. The dynamics of the Jakarta Charter still leaves a long-standing difference by photographing the 7 words